(untitled) (Jurnal Pustaka, 2026)
This research aims to analyze the process of cultural adaptation in Civics studens in the 3rd batch of Independent Student Exchange Program (PMM) at PGRI Yogyakarta University. By using a descriptive approach, this research includes interviews with Civics students who ran the PMM program, Liaison Officer and Nusantara Module Lecturers and MBKM Lecturers of Civics Study Program at Jambi University. The result showed that the process of cultural adaptation in Civics students was influenced by several factors, namely : 1) personal communication, 2) host social communication, 3) ethnic social communication, 4) environment, 5) predisposition. This research provides an in-depth understanding of the impact of cultural adaptation experiences on the attitudes and adaptive behaviors of Civics sutdents through the Independent Student Exchange Program (PMM) and cross-cultural learning.